Barlow’s Transcatheter Edge-to-Edge Repair in Mitral Annular Calcification - Leo Kar Lok Lai, MD; Hussayn Alrayes, DO; Georgi Fram, MD; James C. Lee, MD; John Dawdy, MD; Brian P. O’Neill, MD; Tiberio M. Frisoli, MD; Pedro Engel Gonzalez, MD; William W. O’Neill, MD; Pedro A. Villablanca, MD (JACC: Case Reports, 2025)
Objective: The presence of Barlow’s and mitral annular calcification poses significant challenges in mitral transcatheter edge-to-edge repair (M-TEER). Our case involved a patient with both pathologies who underwent successful 3-dimensional intracardiac echocardiography (ICE)–guided M-TEER technique with the PASCAL Precision system (Edwards Lifesciences). Key Steps: Our case was an 87-year-old woman with underlying percutaneous endoscopic gastrostomy feeding tube, failed transesophageal echocardiogram probe insertion, proceeded with 3-dimensional ICE-guided M-TEER. With fluoroscopic and ICE guidance, one PASCAL P10 was deployed at 12-6 o’clock lateral A2P2 position, a second PASCAL Ace was deployed at 11-5 o’clock at medial A2P2 position, and a third PASCAL Ace was deployed at 10-4 o’clock at A3P3 medial commissure position. Reduced mitral regurgitation occurred from severe to trivial-mild, without significantly increasing the mitral gradient. Potential Pitfalls: One of the tips in this case would be septostomy using the Armada balloon to facilitate manipulation of the ICE inside the left atrium. Careful manipulation of the delivery system under fluoroscopic guidance was also critical in multiple clips strategy, especially when starting the first clip in lateral position. A combination of P10 and Ace devices would likely be the choice in complex mitral anatomy cases. Take-Home Message: Three-dimensional ICE-guided M-TEER with the use of P10 and Ace of PASCAL system in Barlow’s with MAC is feasible with improvement in mitral regurgitation without elevating the mitral gradient.